อุปสงค์นำเข้าข้าวไทยและปัจจัยกำหนดราคาข้าวในตลาดโมเดิร์นเทรดของจีน - Untong, Akarapong; Pongpatcharatorntep, Danaitun; Kaosa-ard, Mingsarn (Asian Journal of Applied Economics, 2013)
บทคัดย่อ บทความนี้นำเสนอการวิเคราะห์อุปสงค์การนำเข้าข้าวไทยของประเทศจีนระหว่าง พ.ศ. 2538-2551 โดยประยุกต์ทฤษฎีอุปสงค์ทางตรงในรูปสมการถดถอยเชิงซ้อน และศึกษาความสัมพันธ์ระหว่างราคาและคุณภาพของข้าวในตลาดโมเดิร์นเทรดของจีน โดยอาศัยแบบจำลอง hedonic price ใช้ข้อมูลรวม 102 ตัวอย่างจากการสำรวจข้าวบรรจุถุงที่ขายอยู่ในตลาดโมเดิร์นเทรดเมืองเซินเจิ้นและกวางโจว ผลการศึกษาพบว่า อุปสงค์นำเข้าข้าวไทยของจีนจัดว่ามีความยืดหยุ่นต่อราคาและเป็นสินค้าปกติเมื่อเทียบกับสินค้านำเข้าอื่นๆ ข้าวหอมมะลิไทยเป็นสินค้าที่มีภาพลักษณ์ดีในตลาดจีน การเลือกซื้อข้าวในตลาดโมเดิร์นเทรด ผู้บริโภคชาวจีนจะให้ความสำคัญกับเรื่องบรรจุภัณฑ์ คุณภาพ ตราสินค้า และความหอมของข้าว ในระยะสั้นภาคเอกชนหรือเจ้าของตราสินค้าควรสร้างตลาดใหม่และสร้างความเชื่อมั่นให้กับผู้บริโภค ภาครัฐควรเข้มงวดในการควบคุมคุณภาพข้าวหอมมะลิ การรักษาภาพลักษณ์ข้าวหอมมะลินับเป็นมาตรการระยะยาวที่สำคัญ โดยควรจัดกิจกรรมส่งเสริมการค้าและการทำตลาดตราสินค้าข้าวหอมมะลิแท้อย่างต่อเนื่อง คำสำคัญ : อุปสงค์นำเข้า, ข้าวหอมมะลิ, แบบจำลอง hedonic price, ตลาดข้าว Abstract This paper presents an analysis of China’s import demand for Thai rice during 1995-2008. A multiple regression method based on a direct demand theory is used for the analysis. The relationship between Thai rice price and quality in the modern trade markets of China is also analyzed using hedonic price model. The survey-based data of 102 samples of packed rice from the modern trade markets in Shenzhen and Guangzhou are used. The results show that the import demand of Thai rice in China is price elastic and classified as a normal goods when compared to otherimported goods. Thai jasmine rice has a good image in the Chinese markets. In the modern trade markets, Chinese consumers expressed preference for rice that is packaged, of high quality, has a brand, and is fragrant. In the short term, private firms or brand owners should establish new markets and try to generate consumer confidence. In support of this, the government should strictly control quality. Maintaining the image of premium jasmine rice is an important long term strategy. This should be done through occasional trade promotion and marketing activities for high quality brands. Keywords : import demand, jasmine rice, hedonic price model, rice market JEL Classification : Q11, Q13